2007
DOI: 10.1007/s00247-007-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumour: prognostic factors, staging, therapy and late effects

Abstract: Wilms tumour is the most common malignant renal tumour in children. Dramatic improvements in survival have occurred as the result of advances in anaesthetic and surgical management, irradiation and chemotherapy. Current therapies are based on trials and studies primarily conducted by large multi-institutional cooperatives including the Société Internationale d'Oncologie Pédiatrique (SIOP) and the Children's Oncology Group (COG). The primary goals are to treat patients according to well-defined risk groups in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 97 publications
3
137
1
2
Order By: Relevance
“…A retrospective analysis by Kaste et al drew attention once again to known risk factors for nephroblastoma recurrence [11]. The prognosis was worsened by unfavorable histopathology with diffuse anaplasia, which were associated with lower sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis by Kaste et al drew attention once again to known risk factors for nephroblastoma recurrence [11]. The prognosis was worsened by unfavorable histopathology with diffuse anaplasia, which were associated with lower sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that certain germline WT1 gene mutations are associated with a more resistant phenotype, which in bilateral cases harbors a higher risk for an eventual anephric status [14,26]. In this case report we describe a 10-month-old African girl with chemotherapy un-responsive bilateral Wilms tumor, with a novel germline WT1 gene splice site mutation in intron 6, who ultimately, underwent sequential bilateral tumor-nephrectomy.…”
Section: Introductionmentioning
confidence: 93%
“…However, it is difficult to determine the respectability of a tumor (3) . Tumor histology and staging represent the main prognostic factors in cases of WT (4) . The tumor staging is defined by surgical and histopathological findings.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two approaches for the initial management of WT are adopted with similar results (3,4) . Such approaches are based on studies developed by two cooperative groups, namely, National Wilms' Tumor Study (NWTS) and International Society of Paediatric Oncology (SIOP).…”
mentioning
confidence: 99%